Carbon emissions, out-of-pocket expenditure and life expectancy of reproductive age women in West Africa - Sikwela, Misery M; Ntshangase, Bhekabantu Alson; Ramsarghey, Kevin; Aderemi, Timothy A (Asian Economic and Financial Review, 2025)
In recent years, many residents of West Africa have been facing a perpetual rise in out-of-pocket expenses alongside environmental pollution, which could instigate serious health challenges for the vulnerable population in the region. Against this backdrop, this study investigated the nexus among carbon emissions, out-of-pocket expenditure, and life expectancy of reproductive-age women within the West Africa subregion from 2000 to 2020. After subjecting the collected data to empirical analysis, the following conclusions evolved from the study: carbon emissions contributed a significant positive effect on the life expectancy of reproductive-age women. However, out-of-pocket expenditure caused a significant reduction in the life expectancy of reproductive women. Arising from these findings, this study makes the following recommendations: whenever policymakers in West Africa want to improve the life expectancy of reproductive women in their region, policies such as health subsidies that would reduce out-of-pocket expenditures to healthcare providers should be implemented. Similarly, policies that would drive the expansion of GDP per capita should be encouraged so that reproductive women in the region would have the economic and financial power to live a quality of life that catalyzes an increase in life expectancy.